Análisis de susceptibilidad a deslizamientos de la vía Villonaco; desde la y sector eucaliptos hasta la intersección vía Villonaco y vía antigua a Catamayo, cantón y provincia de Loja. - Lapo Paredes, Andrea de Lourdes (2016)
This thesis project aims at analyzing landslide susceptibility, which is prone to Via Villonaco from the industry and eucalyptus trees to the intersection via Villonaco old to Catamayo road. For its realization fieldwork and office were executed, among which may be mentioned are: topographic, geological, geomorphological survey and current land use all data obtained were processed in office. In order to meet the geotechnical characteristics of the sector electrical soundings as an indirect method and Test Standard Penetration (SPT) as a direct method were performed to correlate with geology raised above in addition to knowing the presence of water in the sector and resistivity materials. Another additional parameter to these was the landslide inventory, which it did in order to know the number of slides with their morphometric measurements present in the study area besides knowing the area affected thereof. For the map of susceptibility proceeded to the application of deterministic method in which calibration parameters obtained by standard penetration test (SPT) as used: soil density, cohesion, dimensions, angle of internal friction, gravity, density water and soil thickness. Resulting in 4 degrees of stability that are very low jitter (10.8%), low stability (15.01%), moderate stability (12.5%) and high stability (67.34%), and establishing the critical areas (unstable areas and low stability) terrain are generated mainly by influence of water infiltration; areas specifically for the South - East of the study area.